2007
DOI: 10.1007/s00420-007-0188-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation and dietary exposure to polycyclic aromatic hydrocarbons and urinary 1-hydroxypyrene in non-smoking university students

Abstract: Countermeasures to lower PAHs levels in atmosphere has been successful in Japan and more attention should be directed to dietary exposure to PAHs for reducing cancer risk in general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
3
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 17 publications
1
37
3
2
Order By: Relevance
“…Neither did Scherer et al (2000) in a study of 69 subjects including smokers, although they cite inaccuracy of assessing PAH (benzo[a] pyrene) intake as a possible explanation. In nonsmoking, non-occupationally exposed individuals whose dietary intakes were measured, it has been calculated that dietary pyrene intake accounts for between 87.5 and 99.8% of total (inhalation + dietary) dosage ) and more than 90% by Suzuki and Yoshinaga (2007).…”
Section: Dietmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither did Scherer et al (2000) in a study of 69 subjects including smokers, although they cite inaccuracy of assessing PAH (benzo[a] pyrene) intake as a possible explanation. In nonsmoking, non-occupationally exposed individuals whose dietary intakes were measured, it has been calculated that dietary pyrene intake accounts for between 87.5 and 99.8% of total (inhalation + dietary) dosage ) and more than 90% by Suzuki and Yoshinaga (2007).…”
Section: Dietmentioning
confidence: 99%
“…Pyrene is almost always present in the mixture of PAHs people are exposed to, and correlates highly with other common PAHs (Suzuki and Yoshinaga 2007). As such, urinary metabolites of pyrene are often used to assess the internal dose of total PAH exposure (Strickland and Kang 1999;Viau 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the studies conducted to date are limited and have yielded somewhat inconsistent conclusions. Studies conducted in some East Asian regions have revealed that dietary exposure to PAHs contributes more to the overall exposure level of the local population; e.g., for the sum of the 16 EPA prioritycontrolled PAHs (SPAH 16 ) in Tianjin, China (Li et al, 2005), benzo [a] pyrene equivalent PAH (BAP eq ) in Taiyuan, China (Xia et al, 2010(Xia et al, , 2013, and pyrene, benzo [b]fluoranthene, and benzo[a]pyrene in Tokyo, Japan (Suzuki and Yoshinaga, 2007). However, in the United States, the primary routes of exposure to low-molecular-weight PAHs (L-PAHs, generally PAHs with 4 benzene rings), including naphthalene, fluorene and pyrene, were inhalation, whereas BAP exposure was predominantly from food intake (Shin et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…These studies were not limited to industrial areas (Table 3) [6,10,13,15]. In our study, the median concentration of urinary 1-OHP of the subjects in both Japan (0.069 ng/mg creatinine) and in Vietnam (0.417 ng/mg creatinine) were far below the 2.66 ng/mg creatinine threshold proposed by Jongeneelen et al, below which no effects are expected among non-smoking subjects without occupational exposure [18].…”
Section: Pah Exposure Among Subjectsmentioning
confidence: 71%
“…While its detection limit is 0.109 ng/ml, which is considered sufficient for detecting high-level exposures, this may be too high to detect low-level exposures. Given that the lowest reported median 1-OHP among non-occupationally exposed individuals was found to be 0.030 ng/ml, this implies that a more sensitive method with a lower detection limit is required to estimate these very low-level exposures [13]. Subsequent work has therefore been undertaken to improve this method.…”
Section: Introductionmentioning
confidence: 99%